ADVANCE CARE PLANNING AMONG CHINESE AMERICAN OLDER ADULTS: AN EXPLORATORY STUDY. (11th November 2018) - Liu, Y; Sun, F; Marsiglia, F; Roberto, A
Abstract: Objective: This study aimed to improve the engagement of advance care planning (ACP) on end-of-life care among Chinese American older adults. The Health Belief Model (HBM) was applied to explain Chinese American older adults' ACP behaviors consisting of discussion of end-of-life care plans with family members and completion of an advance directive (AD). Method: A cross-sectional survey was conducted through face-to-face interviews on a sample of 319 community-dwelling Chinese-American adults aged 55 and above living in the Phoenix metropolitan areas. Based upon random assignment, 161 participants answered questions regarding discussing end-of-life care plans with family members, while 158 participants answered questions related to AD completion. Hierarchical logistic regression analysis was used to examine the influence of the constructs (e.g., perceived susceptibility and barriers) in the HBM on these two behaviors. Results: Controlling for the effects of gender, age, education, income, religion, and residence length in the U.S., perceived barriers (OR = .23, p < .001) was related to lower likelihood of discussion with family members about end-of-life care plans. Similarly, controlling for the same variables, perceived barriers (OR = .18, p < .05) were significantly related to lower likelihood of completion of an AD. But perceived susceptibility (OR = 5.11, p < .05) was related to higher likelihood of completion of an AD. Implications: The HBM is useful in explaining ACP behaviors among Chinese American older adults. Factors (e.g., perceived susceptibility and barriers) should be considered in designing educational interventions and public awareness campaigns to promote behavior changes regarding ACP.